The picture so far 50 years of painting conservation - Granville, Abigail; Hinde, Laura; Plender, Sophie; Tomlinson, Hayley; Wade, Nancy (Archetype Publications, 2017)
Following on from the success of the British Association of Paintings Conservator-Restorers (BAPCR) conference, 'The Picture So Far: 50 Years of Painting Conservation' post-print texts from the conference are to be published. 'The Picture So Far' examined and celebrated the aspirations and achievements of early conservation pioneers through lectures, posters, and a discussion session. Invited speakers explored conservation practice, philosophy, teaching, technology and professional organisation over the last half century leading the audience to examine the fundamental principles of our profession today and appraise the challenges that will face the next generation of practitioners
Papers from the conference 'The Picture So far...50 Years of Painting Conservation' held at the Royal Institution in London's West End
Keywords: Geschichte; Gemälderestaurierung; Painting / Conservation and restoration / Congresses; Painting / Conservation and restoration; Conference papers and proceedings; Konferenzschrift -- 2013 -- London